SHARIAH GOVERNANCE IN THE DISCLOSURE OF THE ISLAMIC SOCIAL REPORTING INDEX AND GLOBAL REPORTING INDEX IN ISLAMIC BANKING FOR THE PERIOD 2010-2013 - Sunarto, Citra (Universitas Airlangga, 2016)
This study aims to examine the effect of shariah governance, measured by the board of directors of Islamic banks, the shariah supervisory board, and the audit committee, on the disclosure of the Islamic Social Reporting Index (ISRI) and the Global Reporting Index (GRI). Islamic banks currently still use the Social Reporting Index (SRI) and the Global Reporting Index (GRI). This study uses a quantitative method with purposive sampling technique. The analysis techniques used are multiple regression and Independent Samples T-test. The results of this study found that the role of the Islamic bank's board of directors influences disclosure using the ISR index, while the Sharia supervisory board influences disclosure using the GRI index. The results of the independent samples T-test found that disclosure using the ISR index is higher than that using the GRI index.